2020
DOI: 10.1038/s41598-020-76794-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis in familial Alzheimer’s disease of Han Chinese in Taiwan with a predominant mutation PSEN1 p.Met146Ile

Abstract: Mutations in PSEN1, PSEN2, or APP genes are known to be causative for autosomal dominant Alzheimer’s disease (ADAD). While more than 400 mutations were reported worldwide, predominantly PSEN1, over 40 mutations have been reported in Han Chinese and were associated with earlier onset and more affected family members. Between 2002 and 2018, 77 patients in the neurological clinic of Taipei Veterans General Hospital with a history suggestive of ADAD were referred for mutational analysis. We retrospectively collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Research reported 9 cases with the PSEN1 G206D mutation, most of whom had a family history, including 5 patients whose pedigrees were rst reported in France in 2005, with an onset age ranging from 32 to 34 years, though detailed clinical information was lacking 4 . The clinical characteristics of other patients were summarized in Table 1 [5][6][7] . This patient we reported was characterized by initial cognitive impairment, early-onset seizure, no neuropsychiatric symptoms, slow progression, and good response to the medications for cognitive improvement and seizure.…”
Section: Discussionmentioning
confidence: 99%
“…Research reported 9 cases with the PSEN1 G206D mutation, most of whom had a family history, including 5 patients whose pedigrees were rst reported in France in 2005, with an onset age ranging from 32 to 34 years, though detailed clinical information was lacking 4 . The clinical characteristics of other patients were summarized in Table 1 [5][6][7] . This patient we reported was characterized by initial cognitive impairment, early-onset seizure, no neuropsychiatric symptoms, slow progression, and good response to the medications for cognitive improvement and seizure.…”
Section: Discussionmentioning
confidence: 99%
“…We used familial AD (PSEN1 M146I) iPSC-derived NSCs and confirmed that trametinib could induce neuronal differentiation. The PSEN1 M146I mutation is a widespread mutation in AD patients with PSEN1 mutations 56 . Therefore, it is reasonable to expect that trametinib can induce neurogenesis in an AD patient’s brain.…”
Section: Discussionmentioning
confidence: 99%
“…ADAD is caused by mutations or duplications of the amyloid precursor protein ( APP ), mutations in presenilin 1 ( PSEN1 ), or mutations in presenilin 2 ( PSEN2 ), an autosomal dominant inheritance within family members for more than two generations, and an onset earlier than 65 years old [ 4 , 5 ]. More than 400 mutations have been reported on these three genes, but PSEN1 harbors the most mutations, which are also associated with the youngest age at onset with affected individuals typically being 30–50 years old [ 4 , 6 8 ]. In fact, PSEN1 mutations have also been reported in late-onset AD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%